Integrin-beta3 clusters recruit clathrin-mediated endocytic machinery in the absence of traction force - Yu, Cheng-han (Nat Commun, 2015)
The turnover of integrin receptors is critical for cell migration and adhesion dynamics. Here we find that force development at integrins regulates adaptor protein recruitment and endocytosis. Using mobile RGD (Arg-Gly-Asp) ligands on supported lipid membranes (RGD membranes) and rigid RGD ligands on glass (RGD-glass), we find that matrix force-dependent integrin signals block endocytosis. Dab2, an adaptor protein of clathrin-mediated endocytosis, is not recruited to activated integrin-beta3 clusters on RGD-glass; however, it is recruited to integrin-mediated adhesions on RGD membranes. Further, when force generation is inhibited on RGD-glass, Dab2 binds to integrin-beta3 clusters. Dab2 binding to integrin-beta3 excludes other adhesion-related adaptor proteins, such as talin. The clathrin-mediated endocytic machinery combines with Dab2 to facilitate the endocytosis of RGD-integrin-beta3 clusters. From these observations, we propose that loss of traction force on ligand-bound integrin-beta3 causes recruitment of Dab2/clathrin, resulting in endocytosis of integrins.